Development of advanced audiological equipment in India for the identification and diagnosis of the difficult-to-test cases - P, Rama Mohan Babu (Journal of All India Institute of Speech and Hearing)
Considerable progress has been made in audiological testing methods in the past few years with the commencement of production of diagnostic audiometers in the public and private sectors in India. Though these audiometers are satisfactory for cases with simple auditory problems, their scope is rather limited with the difficult-to-test population. These audiometers require a voluntary participation of the patient and as such the responses are subjective in nature. There is a dire necessity for the development of low-cost indigenous equipment with which objective evaluations of hearing can be done. An attempt is made in this paper to explore the possibilities of development of such equipment. A few details of the work carried out in this direction at the B.M, Institute of Mental Health, Ahmedabad are also mentioned